The State of biodiversity in the Caribbean Community : a review of progress towards the Aichi biodversity targets - Edward, Thera, Dr. (CCS GeorgetownGY, 2018)
Highlights achievements, good practices, success stories and lessons learnt that can be shared among the countries in the regions. Presents recommendations for addressing challenges and for mainstreaming biodiversity as a key element of the region's sustainable development.